Criminal Fines For Traffic Violations In The View Of Islamic Law - Setiawati, Sri; Hartati, Sri (UNISSULA Semarang, 2023)
In the realm of Islamic jurisprudence, ulil amri assumes the responsibility of crafting broad regulations, such as those pertaining to traffic and immigration, with the intention of overseeing human conduct and endeavors while averting disorder.It is known that traffic rules are made to protect the interests of road users, even though in reality there are still many road users who violate traffic rules. The government and DPR made regulations contained in Law No. 22 of 2009. This law is considered less than optimal because ordinary people often think that the police decide the amount of the violation fund which is called